The Role of Teachers in The Development of Islamic Religious Education (PAI) Curriculum in Public Junior High Schools - Adila, Alya Ulfa; Sari, Intan Purnama; Adiyono, Adiyono (Pedagogia: Jurnal Ilmiah Pendidikan, 2023)
This article discusses the important role of Islamic Religious Education (PAI) teachers in developing the PAI curriculum at SMPN 4 Sangkuriman-Tanah Grogot. The article highlights the need for teachers to design a curriculum that meets national education standards and student needs. The article also emphasizes the importance of balancing religious and contemporary aspects in the curriculum. Teachers can identify student needs by observing and interviewing students, parents, and fellow teachers. Evaluating student learning outcomes is also crucial to ensure that the curriculum meets student needs. The article cites several studies that explore the role of PAI teachers in improving student motivation, building student character, and increasing teacher professionalism. These studies provide valuable insights into best practices for developing the PAI curriculum at SMPN 4 Sangkuriman-Tanah Grogot.